Changes in Metabolic Hormones in Malaysian Young Adults following Helicobacter pylori Eradication - Theresa Wan-Chen Yap; Alex Hwong-Ruey Leow; Ahmad Najib Azmi; Fritz Francois; Guillermo I Perez-Perez; Martin J. Blaser; Bee-Hoon Poh; Mun-Fai Loke; Khean-Lee Goh; Jamuna Vadivelu (Public Library of Science (PLOS), 2024)
Indexed by Scopus